The dynamin middle domain is critical for tetramerization and higher-order self-assembly - Ramachandran, Rajesh (Nature Publishing Group, 2007)
The large multidomain GTPase dynamin self-assembles around the necks of deeply invaginated coated pits at the plasma membrane and catalyzes vesicle scission by mechanisms that are not yet completely understood. Although a structural role for the ‘middle' domain in dynamin function has been suggested, it has not been experimentally established. Furthermore, it is not clear whether this putative function pertains to dynamin structure in the unassembled state or to its higher-order self-assembly or both. Here, we demonstrate that two mutations in this domain, R361S and R399A, disrupt the tetrameric structure of dynamin in the unassembled state and impair its ability to stably bind to and nucleate higher-order self-assembly on membranes. Consequently, these mutations also impair dynamin's assembly-dependent stimulated GTPase activity.